THE USE OF DIFFERENT METHODS OF TRANSFER PRICING: MATTERS OF CURRENT INTEREST - E. S. Samarina (Финансы: теория и практика, 2017)
Improving tax control over the use of transfer pricing mechanisms in order to minimize tax is a major policy priority for every country. The need for regulation in this area is dictated by the ongoing globalization of business as well as the possibility of implementing complex transactions with residents in different jurisdictions. For the Russian Federation it is particularly important because the largest Russian taxpayers often represent parts of complex, vertically integrated holdings which business and financial activities mostly include cross-border transactions. The existing norms set in Section V.1 of the Tax Code (TC) of the Russian Federation meet the OECD recommendations on transfer pricing. In this connection, it is particularly important to analyze the main trends in regulatory approaches in this field.The world experience proves that transactions involving intangible assets are the most complex ones in transfer pricing. Tax avoidance using international tax planning constitutes a serious risk to tax revenues. On February, 12, 2013 the OECD releases its report «Base Erosion and Profit Shifting» (BEPS) commissioned by the G20 Finance Ministers. One target is to develop an Action Plan aimed to prevent tax base erosion resulting from transfers of intangible assets within the same group. Since Russian companies actively participate in cross-border transactions involving intangible assets, the issue of improving existing standards set in Section V.1 of the Tax Code is highly relevant and timely.The paper considers the concept of transfer pricing as well as the nature and content of an intangible asset in the context of transfer pricing. Moreover, it provides guidance on how to solve tricky problems related to the application of existing tax legislation.